2016
DOI: 10.1126/sciadv.1600855
|View full text |Cite
|
Sign up to set email alerts
|

Social transfer of pain in mice

Abstract: Bystander mice living in the same room as mice with inflammatory- or withdrawal-induced hyperalgesia develop an abnormal pain state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 62 publications
7
134
0
Order By: Relevance
“…This is an important distinction, as cessation of alcohol intake following repeated drug exposure can exacerbate pain sensitivity. This phenomenon, commonly referred to as EtOH withdrawal-induced hyperalgesia (EIH), has been reported in mice (Dhir et al, 2005; Smith et al, 2016), as well as rats (Dina et al, 2000, 2007; Edwards et al, 2012; Fu et al, 2015; Gatch and Lal, 1999; Malec et al, 1987; Roltsch et al, 2017; Shumilla et al, 2005) and humans (Boissoneault et al, 2018; Dodds et al, 1945; Jochum et al, 2010; Riley and King, 2009; Wolff et al, 1942), using a variety of alcohol exposure models. In our CA2BC paradigm, it is unclear whether there were pathological shifts in sensitivity following three weeks of alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important distinction, as cessation of alcohol intake following repeated drug exposure can exacerbate pain sensitivity. This phenomenon, commonly referred to as EtOH withdrawal-induced hyperalgesia (EIH), has been reported in mice (Dhir et al, 2005; Smith et al, 2016), as well as rats (Dina et al, 2000, 2007; Edwards et al, 2012; Fu et al, 2015; Gatch and Lal, 1999; Malec et al, 1987; Roltsch et al, 2017; Shumilla et al, 2005) and humans (Boissoneault et al, 2018; Dodds et al, 1945; Jochum et al, 2010; Riley and King, 2009; Wolff et al, 1942), using a variety of alcohol exposure models. In our CA2BC paradigm, it is unclear whether there were pathological shifts in sensitivity following three weeks of alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ethanol intoxication, but not withdrawal, may increase the short-term consequences of shock. However, work has shown that ethanol withdrawal, not intoxication, can cause increased sensitivity to stressors and tactile sensitivity (Rassnick, Koob, & Geyer, 1992; Smith, Hostetler, Heinricher, & Ryabinin, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In most cases, animals are tested in groups, and social factors can alter results as well. We and others have found that pain sensitivity can be increased (by emotional contagion [110][111][112][113] or social SIH 88,111 ), or decreased (by social SIA 88,110 or social buffering [114][115][116][117][118] ) when animals are in close proximity (through either visual 110 or olfactory 113,119 mechanisms), depending on their social status (siblings, familiars, or strangers) and the threat level determined by their degree of physical access to each other. Our laboratory surprisingly observed that the mere presence of a male (but not female) experimenter in the testing room could produce stress in mice and rats, producing olfactory-mediated SIA that robustly affected apparent "baseline" pain sensitivity 119 .…”
Section: Jeffrey S Mogilmentioning
confidence: 92%